Practical prescribing course: a student evaluation. (February 2014) - Tittle, Vicky; Randall, David; Maheswaran, Vidhya; Webb, Andrew; Quantrill, Simon; Roberts, Michael
Summary Background Prescribing errors occur in up to 10 per cent of junior doctor prescriptions, and medical students feel underprepared for the challenges of prescribing once qualified. A number of studies have looked into the effectiveness of new interventions, in particular pharmacist‐taught prescribing courses, but there is little data on how students perceive these new strategies. The aim of this project was to evaluate a teaching programme of practical prescribing skills, conducted by hospital pharmacists, via a series of focus groups. Methods A pharmacist‐taught course in practical prescribing was introduced to final‐year medical students during clinical placements at five different hospitals. A focus group was conducted at each participating hospital and emerging themes were identified. Results Key emerging themes from the focus group analysis showed that students felt more confident in prescribing after completing the course. Students valued the opportunity to gain practical prescribing experience by using problem‐based exercises, which encouraged them to prescribe on real drug charts, or to spot prescribing errors or drug interactions on charts constructed by pharmacists. Pharmacists were felt to be knowledgeable and approachable teachers. Students highlighted controlled drug prescriptions and familiarity with the British National Formulary (BNF) as key topics that hadn't been covered in conventional pharmacology teaching. Discussion A practical prescribing course can help prepare medical students by giving them the tools to tackle complex prescribing scenarios. Pharmacists as teachers were well received, and specific topics, including controlled drug prescribing and using sample drug charts, should be the focus of these types of courses.